Confocal laser scanning and 3D reconstruction methods for the subsurface damage of polished optics. (January 2021) - Sun, Huanyu; Wang, Shiling; Bai, Jinxi; Zhang, Jianpu; Huang, Jin; Zhou, Xiaoyan; Liu, Dong; Liu, Chong
Highlights: Confocal laser scanning and 3D reconstruction methods for the detection of subsurface defects. 3D scanning in a small area by a galvo and piezo stage, and sub-aperture scanning in a large area by a XY stage. Sub-aperture scanning widens the imaging field of view while ensuring the accuracy. A modified reconstruction algorithm for the subsurface defects with low memory footprint and running time. Abstract: The subsurface damage (SSD) of optics is one of the key factors limiting the increase of energy density of high-power solid-state lasers. Because of the characteristics of small size, low density and wide distribution, it is difficult to detect the SSD of large polished optics with high-accuracy. Confocal laser scanning and three-dimensional (3D) reconstruction methods are proposed in this paper. 3D scanning in a small area is realized by a galvo and piezo stage, and sub-aperture scanning in a large area is realized by a XY stage. Sub-aperture images are stitched together to construct a volume data field, and then a modified Marching Cubes (MC) algorithm is used for 3D reconstruction. Simulations and experimental results show that the algorithm runs faster with low memory footprint, and morphologies of SSDs are displayed intuitively and accurately. The proposed methods provide quantitative evaluations such as the positions, depths and cross-sectional areas of SSDs.